2021
DOI: 10.1039/d0nr08757b
|View full text |Cite
|
Sign up to set email alerts
|

Iron-based nanoparticles for MR imaging-guided ferroptosis in combination with photodynamic therapy to enhance cancer treatment

Abstract: Ferroptosis therapy, which applies ferroptotic inducers to produce lethal lipid peroxidation and induce the death of tumor cells, is regarded as a promising therapeutic strategy for cancer treatment. However, there...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 58 publications
1
69
0
1
Order By: Relevance
“…In another study, in which ultrasmall CaO 2 and Fe 3 O 4 were co-loaded on to dendritic mesoporous silica NPs, researchers showed that these particles can achieve tumor specialized localization and induction of Fenton reaction, thus triggering ferroptosis ( Li and Rong, 2020 ). The Fe 3 O 4 -PLGA-Ce 6 nanosystem, which dissociates in acidic TME, and the Fe 2+ -based metal–organic framework, which delivers Fe 2+ to cancer cells, can also promote the Fenton reaction and facilitate ferroptosis ( Xu et al, 2020b ; Chen Q. et al, 2021 ).…”
Section: Ferroptosis and The Tumor Microenvironmentmentioning
confidence: 99%
“…In another study, in which ultrasmall CaO 2 and Fe 3 O 4 were co-loaded on to dendritic mesoporous silica NPs, researchers showed that these particles can achieve tumor specialized localization and induction of Fenton reaction, thus triggering ferroptosis ( Li and Rong, 2020 ). The Fe 3 O 4 -PLGA-Ce 6 nanosystem, which dissociates in acidic TME, and the Fe 2+ -based metal–organic framework, which delivers Fe 2+ to cancer cells, can also promote the Fenton reaction and facilitate ferroptosis ( Xu et al, 2020b ; Chen Q. et al, 2021 ).…”
Section: Ferroptosis and The Tumor Microenvironmentmentioning
confidence: 99%
“…Recently discovered ferroptosis-inducing agents mainly include iron-based materials (e.g. inorganic iron-involved nanoparticles (NPs), Fe-metal–organic frameworks (Fe-MOFs), iron storage or transport proteins) [ 1 , 3 , 20 , 24 26 ] and certain small molecule drugs (e.g. sorafenib (SRF), erastin, sulfasalazine, artemisinin) [ 23 , 27 29 ], the former accelerating iron-catalyzed ROS production and the latter inhibiting GSH biosynthesis and then decreasing glutathione peroxidase 4 (GPX4, the lipid repair enzyme) expression, eventually leading to large amounts of intracellular LPO accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticle (NP) platforms offer an unmatched potential for tumor-targeting simultaneous delivery of PS, exogenous iron and small GSH/GPX4 reduction molecule [ 30 32 ]. Recently, several Fe-MOFs or Fe-based inorganic NPs have been emerged for PDT and ferroptosis combining therapy, achieving significantly enhanced therapeutic outcomes in tumor oxidation treatments [ 11 , 20 , 26 29 ], however, the biocompatibility, tumor-targeting capacity and clinical translation prospect of which still exist great concerns. Additionally, these nanosystems utilized the acid condition or high concentration of matrix metalloproteinase (MMP) of TME to trigger cargo release, but these differentiations between normal tissues and tumor tissues are not significant enough and easily be affected by the tumor heterogeneity [ 33 – 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the speci c coordination properties between introduced Fe 2+ /Fe 3+ with Fe-coordination proteins, doping biocompatible Fe 2+ /Fe 3+ into silica framework (Fe-HMON NPs) could further improve its biodegradability [36]. However, traditional iron delivery nanomaterials usually exhibit nonspeci c effects, which are mainly delivered through enhanced permeability and retention effects may cause signi cant side effects when applied in vivo [37]. Transferrin is an endogenous protein that can transport Fe 3+ to cells with overexpression of the transferrin receptor [38].…”
Section: Introductionmentioning
confidence: 99%